Antifungal activity of plant and compost extracts and preparations based on tree bark - Elena Petrović; Karolina Vrandečić; Sara Godena; Jasenka Ćosić (Journal of Central European Agriculture)
The escalating global demand for food, propelled by population growth, necessitates increased use of plant protection products. However, heavy reliance on chemical pesticides poses sustainability challenges due to their persistence in the environment and potential toxicity to humans and wildlife. To address these concerns, there is a growing shift towards sustainable and eco-friendly plant protection measures, notably biological preparations. This paper explores the potential of alternative methods, particularly biological preparations, for plant protection. It delves into three main categories: plant extracts, compost extracts, and tree bark-based preparations. Plant extracts, derived from sources like nettle, brown algae, and horsetail, exhibit promising antifungal and antibacterial properties, bolstering plant resistance against pathogens. Compost extracts, rich in diverse microbial populations, offer soil enhancement and disease suppression benefits. Additionally, preparations based on tree bark, abundant in phenolic compounds, demonstrate antimicrobial effects against various pathogens. Although some biological preparations are more effective than chemically produced ones, continued research and development of these alternatives are needed to ensure their effectiveness and availability.